Entre o poético e o histórico: interlocuções de Cecília Meireles com a educação brasileira - Nascimento, Regina Lúcia da Silva (2013)
This work aims to study Cecilia Meireles educational chronicles published from 1930 to 1940 in two newspapers from Rio de Janeiro: Diário de Notícias and A Manhã. In order to analyze the educational, social and historical concepts expressed in this kind of literary genre published in the media, a content analysis, which is a methodological tool that includes the descriptive, inferential and interpretive phases, was adopted in order to create meanings from traces found in the course of reading of the corpus that makes this study. This procedure allowed the exploration of two categories of analysis: the socio-historical process and the educational action. The making of the theoretical framework contemplated aspects related to Education, Cultural History, Reading and Literature, which guided the development of the three chapters of this thesis. In Chapter I, a profile of Cecilia Meireles was built in order to highlight her projection in different activities in the socio-historical context in which she lived. In Chapter II, an analysis was conducted on the dialogues Cecilia Meireles kept with the Brazilian educational context during the 1930 s and the 1940 s as a journalist, educator and as a signatory of the Manifesto dos Pioneiros da Educação Nova (Manifest of the Pioneers of New Education), a movement that attributed educational and social purposes to schools. In Chapter III, the dialogues Cecilia Meireles kept with the training of educators and learners, education and citizenship were analyzed. For her, both the knowledge produced by formal education as well as the artistic and cultural expressions such as art, cinema, folklore, newspaper, literature, music, samba and drama can contribute to the formation of the individual as a whole. It can be concluded that several themes and issues discussed by Cecilia Meireles during Getúlio Vargas government are still present in academic debates and contemporary public policies. Therefore, resuming the dialogue with the educational thinking of Cecília Meireles and offering a new meaning to it, at the present time, can contribute significantly to the rethinking of multiple dimensions of education and teaching. It is a more than deserved tribute to one of the greatest expressions of both the feminine Literature and the History of Education in Brazil.